Desenvolvimento de novas estratégias para a gestão do patrimônio utilizando modelo integrado de monitoramento ambiental e físico com modelagem 3d. - Leal, Ranavalo de Araújo (2024)
Heritage conservation management of historic buildings is of great importance to society, as it perpetuates local culture and identity in political, social, economic and urban contexts. However, the major trend in the current Brazilian scenario is historic buildings in severe stages of structural deterioration, especially on their façades, due to pathological manifestations triggered by physical, chemical and biological agents. It is known that heritage restoration processes are costly and require skilled labor. The study will be carried out at the Soledade Palace, where the Museum of Archaeology and Natural Sciences of the Catholic University of Pernambuco is located, in the Boa Vista neighborhood, Recife, Pernambuco. Physical analysis (façade damage maps using the GUT method), environmental (collection and quantitative and pathogenic analysis of microorganisms present on the façades) and modeling (digital photogrammetry to analyze the difficulty of reconstructing deteriorated parts of the façades) studies will be carried out. The facades of the Soledade Palace are suffering greatly from the high incidences of pathological manifestations, biological infestations and multiple occurrences of ornamental deterioration, especially on the south-west facade, the main facade of the building. The level of the historic heritage quality index will worsen qualitatively if urgent revitalization activities do not take place. The aim of the study is to build a new management strategy by obtaining a new integrated method of analysis according to the results of the parameters under study so that it is possible to understand the level of conservation quality of the historic heritage to facilitate the prioritization of decisions made by the manager on structural restoration and façade maintenance activities.